Scoping review: Health needs of the family caregivers of elderly stroke survivors. (6th April 2021) - Felix, Mark Stephan; Le, Thi Ngoc Phuc; Wei, Min; Puspitasari, Dewi Cahyani
Abstract: This scoping review mapped out the relevant literature, identified gaps and made suggestions on the subject of the health needs of family caregivers (FC) of elderly stroke survivors (ESS). The authors utilised the PRISMA‐ScR checklist to guide the scoping review. The databases PubMed, Elsevier and BioMed Central were searched for academic articles published in the English Language between the years 2010 and 2020 that met a pre‐set criteria of content on the health needs of FC of ESS. The process of selection of sources of evidence based on screening and eligibility of evidence reduced the initially identified 13, 303 sources of evidence in the searched databases to five sources of evidence. The content of these five sources of evidence was mapped out on a charting table where data was summarised and synthesised first individually and then collectively by the authors. Repetitive and irrelevant data were removed collectively by the authors from the charting table. The gaps identified were a paucity of research on the subject of health needs of FC of ESS, lack of longitudinal and mixed‐methods research on the health needs of FC of ESS, sparse use of social sciences perspectives and theories, research that addresses specific physical and mental health concerns beyond general descriptions and gaps in information, social networks, interventions, health policy and systems. Future research directions were suggested and a limitation of this scoping review are addressed in the discussion.